Genome-wide meta-analysis identifies 127 open-angle glaucoma loci with consistent effect across ancestries - Puya Gharahkhani (Nature Portfolio, 2021)
Primary open-angle glaucoma (POAG) is highly heritable, yet not well understood from a genetic perspective. Here, the authors perform a meta-analysis of genome-wide association studies in 34,179 POAG cases, identifying 44 previously unreported risk loci and mapping effects across multiple ethnicities.